Engineering Smut Resistance in Maize by Site-Directed Mutagenesis of LIPOXYGENASE 3 - Pathi, Krishna Mohan; Rink, Philipp; Budhagatapalli, Nagaveni; Betz, Ruben; Saado, Indira; Hiekel, Stefan; Becker, Martin; Djamei, Armin; Kumlehn, Jochen (Frontiers in Plant Science, 2020)
Biotic stresses caused by microbial pathogens impair crop yield and quality if not restricted by expensive and often ecologically problematic pesticides. For a sustainable agriculture of tomorrow, breeding or engineering of pathogen-resistant crop varieties is therefore a major cornerstone. Maize is one of the four most important cereal crops in the world. The biotrophic fungal pathogen Ustilago maydis causes galls on all aerial parts of the maize plant. Biotrophic pathogens like U. maydis co-evolved with their host plant and depend during their life cycle on successful manipulation of the host's cellular machinery. Therefore, removing or altering plant susceptibility genes is an effective and usually durable way to obtain resistance in plants. Transcriptional time course experiments in U. maydis-infected maize revealed numerous maize genes being upregulated upon establishment of biotrophy. Among these genes is the maize LIPOXYGENASE 3 (LOX3) which has been previously shown to be a susceptibility factor for other fungal genera as well. Aiming to engineer durable resistance in maize against U. maydis and possibly other pathogens, we took a Cas endonuclease technology approach to generate loss of function mutations in LOX3. lox3 maize mutant plants react with an enhanced PAMP-triggered ROS burst implicating an enhanced defense response. Homozygous lox3 mutant plants exposed to U. maydis show significantly decreased susceptibility. This finding was corroborated by U. maydis infection assays using a transposon mutant lox3 maize line, which further substantiated that LOX3 is a susceptibility factor for this important maize pathogen.